Indus Journey : A Personal View of Pakistan - Imran Khan (London Chatto & Windus, 1990)
In April 1989, Imran Khan set out to travel throughout Pakistan, from the mouth of the great Indus river, following the 10,000 miles to its source in the Himalayas. This is an account of his trip in which his anecdotes and observations give an insight into Pakistan's past and present.
Include Color Illustration and Index
Keywords: Travel -- Pakistan